Analysis of the influence of iron tailings sand on the properties of concrete mixtures and cyclic compressive behavior - Liang Chen; Yu Tang (Scientific Reports)
Abstract This study investigates the effects of varying iron tailings sand (ITS) content on the workability, mechanical properties, and cyclic compressive behavior of concrete. The results show that increasing ITS content reduces slump and increases water absorption and pressure bleeding rate, with workability dropping below standard thresholds when ITS exceeds 40%. Compressive strength improves with ITS content up to 40%, reaching a maximum of 45.6 MPa, followed by a decline at higher replacement levels. Cyclic loading tests reveal that concrete with 30–40% ITS exhibits enhanced energy dissipation, deformation capacity, and stable hysteresis behavior. Statistical analysis confirms the significance of strength variation across mixes (p < 0.01). The study identifies 30–40% ITS as the optimal range for balancing strength, ductility, and durability. These findings contribute to the sustainable utilization of metallurgical waste in structural concrete and offer practical guidance for its application in seismic-resistant and cyclic load-bearing structures.